Case report of syringohydromyelia and steroid responsive meningitis -arteritis - Parra-Guayasamín, Sandra Gabriela; Larrea, María Gracia (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
Steroid-responsive arteritis meningitis (SRMA) is an immune-mediated disease of the leptomeninges and its associated blood vessels that usually responds to corticosteroids in canines. It is an inflammatory disease that causes cervical hyperesthesia and usually occurs in young dogs of large and medium breed with racial predisposition in Bernese, beagle, whippet, so it is thought to have genetic predilection. A 10 year old beagle patient with progressive neurological signs was received in the clinic with a normal hemogram, blood chemistry showed slightly elevated alanine aminotransferase, elevated gamma-glutamyl transferase and decreased bile acids, the rest of the values were within range. In the cerebrospinal fluid (CSF), there was an absence of infectious agents, pleocytosis 45 nucleated cells/ul, with 60% of degenerated neutrophils and 40% of lymphocytes and the presence of erythrocytes, the laboratory reports a neutrophilic pleocytosis. Magnetic resonance imaging (MRI) of the cervical spinal cord, without contrast shows hyperintense areas in several cervical segments, there is also an area with hyperintensity with increased diameter of the ependymal duct at the medullary level in the transverse, sagittal and coronal section in C2-C3 and C4 of the T2-weighted MRI, compatible with syringohydromyelia.  Finally, he was diagnosed with chronic AMSR, which in turn could be the cause of meningeal fibrosis due to the inflammatory process and this could cause CSF flow obstruction, resulting in cervical syringohydromyelia.
Keywords: Syringohydromyelia; magnetic resonance imaging; cerebrospinal fluid; pleocytosis and AMSR / SRMA